Web services security development and architecture [ theoretical and practical issues - Fernandez-Medina, Eduardo , 1973-; Gutierrez, Carlos , 1977-; Piattini, Mario , 1966- (Gale virtual reference library, 2010)
"This book's main objective is to present some of the key approaches, research lines, and challenges that exist in the field of security in SOA systems" -- Provided by publisher